Standardized, systemic phenotypic analysis of UmodC93F and UmodA227T mutant mice - Kemter, Elisabeth Gabriele; Prückl, Petra; Rathkolb, Birgit; Micklich, Kateryna; Adler, Thure; Becker, Lore; Beckers, Johannes; Busch, Dirk H.; Götz, Alexander A.; Hans, Wolfgang; Horsch, Marion; Ivandic, Boris; et al. (PLOS ONE, 2013)
Uromodulin-associated kidney disease (UAKD) summarizes different clinical features of an autosomal dominant heritable disease syndrome in humans with a proven uromodulin (UMOD) mutation involved. It is often characterized by hyperuricemia, gout, alteration of urine concentrating ability, as well as a variable rate of disease progression inconstantly leading to renal failure and histological alterations of the kidneys. We recently established the two Umod mutant mouse lines UmodC93F and UmodA227T on the C3H inbred genetic background both showing kidney defects analogous to those found in human UAKD patients. In addition, disease symptoms were revealed that were not yet described in other published mouse models of UAKD. To examine if further organ systems and/or metabolic pathways are affected by Umod mutations as primary or secondary effects, we describe a standardized, systemic phenotypic analysis of the two mutant mouse lines UmodA227T and UmodC93F in the German Mouse Clinic. Different genotypes as well as different ages were tested. Beside the already published changes in body weight, body composition and bone metabolism, the influence of the Umod mutation on energy metabolism was confirmed. Hematological analysis revealed a moderate microcytic and erythropenic anemia in older Umod mutant mice. Data of the other analyses in 7-10 month-old mutant mice showed single small additional effects.